Detecção do papilomavírus humano e análise de P16ink4a em carcinomas colorretais - Libera, Larisse Silva Dalla (2021)
Introduction: Colorectal cancer (CRC) is one of the most prevalent cancers, being the second leading cause of cancer death worldwide. Despite the well established role of human papillomavirus (HPV) in anal cancer, its involvement in colon and rectum tumors is still a controversial issue. Objective: To investigate the presence of HPV and the expression of p16INK4a in colorectal carcinomas and in non-tumor controls, and to describe the prevalence of HPV in colon, rectum and anal cancers through a literature review. Methodology: This is a retrospective observational study that used clinical and pathological data and paraffin embedded specimens from patients with and without colorectal carcinoma. HPV detection was accomplished by PCR, genotyping by reverse hybridization, and the expression of the cellular protein p16INK4a was investigated by immunohistochemistry. A systematic review was also carried out on the databases, PUBMED, LILACS and SCIELO, according to PRISMA recommendations. Results: HPV was detected in 13% of the cases and the most prevalent genotype was HPV 16. The virus was not detected in both control groups. A high expression of p16INK4A was observed in 30% of the cases, but it was not associated with the presence of HPV. The overall survival was 53.3% and it was influenced by the prognostic factors such as advanced staging, lymph node and distant metastasis. Regarding the literature review, data were collected from 42 studies (5,834 samples). HPV was detected in 88.9% of anal cancer cases, and in 10.9% of colorectal cancer cases. Genotypes 16 and 18 were the most prevalent in both tumors. HPV was associated with anal squamous cell carcinoma (p <0.0001) and more prevalent in women with anal cancer (p <0.0001). Conclusion: Our results demonstrate that HPV is unlikely to be involved in colorectal carcinogenesis, and that p16INK4a expression is not a relevant biomarker of transcriptionally active HPV infection in CCR. The literature review data reassures the HPV causal relationship in anal cancer, but not in colorectal cancer.